Sliding mode controller design for trajectory tracking of a non-holonomic mobile robot with disturbance. (November 2018) - Goswami, Niraj Kumar; Padhy, Prabin Kumar
Abstract: This paper develops sliding mode controller for the trajectory tracking of a non-holonomic differentially driven wheeled mobile robot (DDWMR) with measurement noise, frictional disturbances and model uncertainties. The proposed controller is designed with the help of an existing Proportional-Integral (PI) sliding surface for trajectory tracking followed by a new Proportional-Integral-Derivative (PID) sliding surface for velocity tracking. The PI and PID sliding surfaces are based on the kinematic model and dynamic model of the robot, respectively. An adjustable gain switching controller is incorporated for minimizing the effect of disturbances and uncertainties. The closed loop stability of the system is proved using Lyapunov stability criteria. The proposed controller is validated with the help of numerical examples and real-time experiments on DDWMR.